Innovating agricultural marketing: credit codes as a new tool to boost sales of place-of-origin products - Wei, Hengshu; Li, Guilong; Liang, Xv; Li, Yuwei; Huang, Qiuli (Frontiers in Sustainable Food Systems, 2025)
IntroductionMerchants often use the place-of-origin as a promotional tool for regionally distinctive agricultural products, yet consumers face challenges verifying origin authenticity. Prior research has centered on detection technologies to build trust, neglecting merchant credibility’s impact. This study explores the role of China’s Credit Information Network (CIN) credit codes in consumer purchasing behavior, an unexplored area.MethodsThree experiments, with student and general consumer participants, were conducted. Experiment 1 evaluated credit codes’ direct effect on purchase intentions. Experiment 2 examined perceived brand authenticity’s mediating role. Experiment 3 explored regulatory focus (promotion vs. prevention) as a moderator.ResultsCredit codes on packaging boost perceived brand authenticity, enhancing willingness to buy place-of-origin agricultural products. They have a stronger impact on prevention-focused consumers. These findings suggest that credit codes serve as effective tools in communicating credibility and authenticity, thereby influencing consumer purchasing decisions.DiscussionThis study validates credit codes as an effective credibility cue in agricultural product marketing, leveraging signaling theory to elucidate their role in fostering consumer trust. The findings highlight the importance of both credibility mechanisms at the merchant and system levels and technological verification tools. Practically, it supports wider credit code adoption in agricultural marketing and offers strategic insights.